Occurrence and behavioral rhythms of the endangered Acadian redfish (Sebastes fasciatus) in the Sambro Bank (Scotian Shelf) - Grinyó, Jordi; Aguzzi, Jacopo; Kenchington, Ellen; Costa, Corrado; Hanz, Ulrike; Mienis, Furu (Frontiers in Marine Science, 2023)
The genus Sebastes is a morphologically and ecologically diverse genus of rockfish characterized by high longevity, late-maturity and low natural mortality. On the northwest Atlantic continental shelf, the Acadian redfish (Sebastes fasciatus) is the most common rockfish species above 300 m depth. This species has been widely exploited resulting in the depletion or collapse of most of its stocks. Management of long-lived species with intricate life-history characteristics is challenging and requires highly integrated biological and oceanographic monitoring, which allow the identification of environmental drivers and demographic and behavioral trends. The present study uses high-temporal resolution imaging and environmental data, acquired with an autonomous lander deployed for 10-months at the Sambro Bank Sponge Conservation Area (Scotian Shelf) to elucidate S. fasciatus temporal dynamics and behavioral trends in response to near-bed environmental conditions. S. fasciatus, mostly displayed passive locomotion and static behaviors, in common with other shelf-dwelling Sebastes species. Structural complexity provided by sponges positively influenced S. fasciatus presence. Fish used sponges to avoid being dragged by bottom currents. Hydrodynamics appear to act as a synchronizing factor conditioning its swimming behavior. S. fasciatus total counts exhibited a seasonal shift in rhythm’s phase likely reflecting changes in lifestyle requirements. This study provides new insights on S. fasciatus dynamics and behavior. Nonintrusive monitoring approaches, such as the one used in this study, will be key to monitor this threatened species populations. Especially, since it is expected that S. fasciatus will experience distribution shifts to higher latitudes due to future climate stressors.